Characteristics, occurrence and fate of non-point source microplastic pollution in aquatic environments. (20th March 2022) - Tan, Yanping; Dai, Jiangyu; Wu, Xiufeng; Wu, Shiqiang; Zhang, Jianmin
Abstract: Microplastics (MPs) entering aquatic environments from non-point sources are receiving global attentions and are difficult to manage. To control the accumulation of MPs in aquatic environments, it is necessary to investigate their abundances, characteristics and removal methods. Although previous studies had summarized characteristics and removal of MPs in stormwaters, there is still a large knowledge gap about the occurrence and fate of non-point source MPs in aquatic environments. The detection methods, characteristics and abundances of non-point source MPs in aquatic environments were reviewed. Lack of reliable and uniform detection methods is the main challenge for present studies. Considering the critical need to focus on water-energy-environment nexus, constructed wetland (CW) was put forward as a sustainable and efficient treatment technology to remove non-point source MPs. Removal performances of MPs in different structural components of CWs were also critically compared. According to literatures, the magnitude of abundances for non-point source MPs in water samples ranges from 10 −1 to 10 2 items L −1 . Fibers, fragments (including tire/road wear), films are dominant shapes of non-point source MPs, while polyethylene, polypropylene, polyethylene terephthalate, and polystyrene are main polymer types. The main measures to remove non-point source MPs are precipitation, filtration and ingestion in CWs. Compared with other shapes, the removal efficiency of fibers in CWs is relatively lower. Most of removed MPs always remain at the entrance of CWs, which may cause clogging of substrates. Vegetation and organisms in CWs may enhance the removal efficiency of MPs by capturing and ingesting as well as preventing substrates clogging. Additionally, possible research gaps and key directions are also given for future considerations. Standardization and efficient treatment materials are future research priorities. Graphical abstract: Image 1 Highlights: Detection, features and fate of non-point source microplastics are reviewed. Abundance of non-point source microplastics ranges from 10 −1 to 10 2 items L -1 . Constructed wetland is most effective to remove non-point source microplastics. Filtration, settlement and ingestion remove microplastics in constructed wetlands. Standardization and efficient treatment materials are future research priorities.